A novel mitochondrial inhibitor blocks MAPK pathway and overcomes MAPK inhibitor–resistance in melanoma. - Vashisht Gopal, Y. N. (Clin Cancer Res, 2019)
PURPOSE: To determine if inhibition of mitochondrial oxidative phosphorylation (OxPhos) is an effective strategy against MAPK pathway inhibitor (MAPKi)-resistant BRAF-mutant melanomas. EXPERIMENTAL DESIGN: The anti-melanoma activity of IACS-010759 (OPi), a novel OxPhos complex I inhibitor, was evaluated in vitro and in vivo. Mechanistic studies and predictors of response were evaluated using molecularly and metabolically stratified melanoma cell lines. (13)C-labeling and targeted metabolomics were used to evaluate the effect of OPi on cellular energy utilization. OxPhos inhibition in vivo was evaluated non-invasively by [(18)F]-FAZA PET imaging. RESULTS: OPi potently inhibited OxPhos and the in vivo growth of multiple MAPKi-resistant BRAF-mutant melanoma models with high OxPhos at well-tolerated doses. In vivo tumor regression with single agent OPi treatment correlated with inhibition of both MAPK and mTOR complex I activity. Unexpectedly, anti-tumor activity was not improved by combined treatment with MAPKi in vitro or in vivo. Signaling and growth inhibitory effects were mediated by LKB1-AMPK axis, and proportional to AMPK activation. OPi increased glucose incorporation into glycolysis, inhibited glucose and glutamine incorporation into the mitochondrial tricarboxylic acid cycle, and decreased cellular nucleotide and amino acid pools. Early changes in [(18)F]-FAZA PET uptake in vivo, and the degree of mTORC1 pathway inhibition in vitro, correlated with efficacy. CONCLUSIONS: Targeting OxPhos with OPi has significant anti-tumor activity in MAPKi-resistant, BRAF-mutant melanomas, and merits further clinical investigation as a potential new strategy to overcome intrinsic and acquired resistance to MAPKi in patients.